2018
DOI: 10.5093/clysa2018a1
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad a Largo Plazo de la Terapia de Grupo Cognitivo-conductual del Alcoholismo: Impacto de la Patología Dual en el Resultado del Tratamiento

Abstract: El objetivo de este estudio fue analizar el resultado del tratamiento cognitivo-conductual grupal llevado a cabo en un centro ambulatorio para el tratamiento de las adicciones. La muestra estuvo compuesta por 130 hombres con trastorno por dependencia al alcohol. Se evaluaron los casos que reinician tratamiento tras el alta terapéutica en un rango de tiempo desde los dos años como mínimo hasta los 18. El 56.2% de la muestra finalizó el tratamiento con alta terapéutica, de los cuales el 75.3% no volvieron a inic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
2
0
3
Order By: Relevance
“…In the present study, 50% of patients remained abstinent after 7.3 months of treatment and 40% were abstinent at the end of the therapeutic community treatment. This finding could be considered a good rate of success, similar to other rates of abstinence in comparable alcohol dependence programs (Martínez-González et al , 2018). The finding is also in line with the results of a study by Martínez-González et al (2018), which showed that 56.2% of patients finished treatment and were discharged; in fact, 75.3% of patients remained abstinent after discharge from the individual, group or community treatment.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In the present study, 50% of patients remained abstinent after 7.3 months of treatment and 40% were abstinent at the end of the therapeutic community treatment. This finding could be considered a good rate of success, similar to other rates of abstinence in comparable alcohol dependence programs (Martínez-González et al , 2018). The finding is also in line with the results of a study by Martínez-González et al (2018), which showed that 56.2% of patients finished treatment and were discharged; in fact, 75.3% of patients remained abstinent after discharge from the individual, group or community treatment.…”
Section: Discussionsupporting
confidence: 81%
“…This finding could be considered a good rate of success, similar to other rates of abstinence in comparable alcohol dependence programs (Martínez-González et al , 2018). The finding is also in line with the results of a study by Martínez-González et al (2018), which showed that 56.2% of patients finished treatment and were discharged; in fact, 75.3% of patients remained abstinent after discharge from the individual, group or community treatment. Another important goal is to determine the optimal duration of alcohol dependence programs to ensure that most patients remain abstinent.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…-Si bien se asumía que el tratamiento de los tp fracasaba (Vaillant y Perry, 1980), se ha podido constatar cómo la psicoterapia cognitivo-conductual es efectiva en el tratamiento de estos pacientes (Martínez-González et al, 2018).…”
Section: Marco Teóricounclassified